Comprehensive Study of Sexual Reproduction in Nicotiana tabacum Plants Overexpressing H2O2-Producing Enzymes: Superoxide Dismutase and Choline Oxidase - Anna Podobedova; Ekaterina N. Baranova; Alexander A. Gulevich; Inna A. Chaban; Maria Breygina (Plants, 2025)
Transgenic tobacco plants with additional enzymes producing hydrogen peroxide (H2O2)—superoxide dismutase from Arabisopsis thaliana and choline oxidase from Arthrobacter globiformis—have increased resistance to stress factors, which was demonstrated previously, but their reproductive potential has not been studied to date. Superoxide dismutase converts superoxide radical into H2O2, and choline oxidase catalyzes the oxidation reaction of choline to form betaine aldehyde, which is subsequently converted into glycine betaine and H2O2. We found that the addition of both exogenous genes stimulated growth of the floral organs: petals, styles, and stamens. However, the reproductive potential of the transgenic plants was different. Thus, the introduction of the superoxide dismutase gene FeSOD significantly increased pollen germination in vitro, in vivo, the size of fruits, and the number of seeds. At the same time, the insertion of the CodA gene resulted in the production of abnormal pollen with low germination in vitro. The female reproductive potential system in these plants was not affected. Thus, shifting the ROS balance towards hydrogen peroxide not only increases tobacco stress resistance but also stimulates reproductive success. Glycine betaine production disrupts pollen formation, although such plants show increased resistance to osmotic stress.